Historical distribution of the otter (Lutra lutra) in north‐east China according to historical records (1950–2014). Issue 3 (4th April 2016) - Zhang, Rui; Yang, Li; Laguardia, Alice; Jiang, Zhe; Huang, Mujiao; Lv, Jiang; Ren, Yueheng; Zhang, Wei; Luan, Xiaofeng
Abstract: 1. The Eurasian otter ( Lutra lutra ) has undergone a dramatic decline throughout the 20th century in China, especially in the North East. However, the dynamics responsible for the reduction in the distribution of otters in this region since the 1950s is still unclear. Such uncertainty and insufficient information can hinder effective conservation strategies. 2. A study was conducted using historical documents to attempt an evaluation of the status of otter populations in north‐east China between 1950 and 2014. The data suggest that otters were widely distributed with abundant populations in north‐east China in the 1950s, particularly in the area of the Songhua River basin and the Ussuli River basin. 3. Compared with the 1950s, the number of records in 2014 has fallen by 92%. Otter populations are fragmented and mainly restricted to national nature reserves, leaving little optimism for their future. 4. More broadly, this research demonstrates that recovering information from local historical documents can be a useful and reliable way to overcome the limits caused by lack of data. Copyright © 2016 John Wiley & Sons, Ltd.